PENGARUH MODEL PEMBELAJARAN ARIAS TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS X DI SMK IT AL-JUNAEDIYAH - Rahmawati, Sri Dewi; Setiadi, David; Agustiani, Tanti (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to implement the Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) learning model in the experimental class in the poetry writing ability of class X students at Al-Junaediyah IT Vocational School. The samples taken by researchers used cluster random sampling. The method used is quantitative experimentation in order to examine the effect of a treatment on the symptoms of a group and can be compared with other groups given different treatments. Meanwhile, the data collection used by researchers, apart from collecting poetry writing test results in the pretest (initial test) and posttest (final test), also took observation data through observation sheets as student observations during the learning process and documentation in the form of photos or drawings. in the classroom environment. The results of this research show a significant effect, seen from the final average data that the experimental class got 84.83 and the control class got 66.03. Thus, the final results show significant differences between classes that were given treatment and those that were not given treatment. Apart from that, the hypothesis results also show significance where H1 is accepted and H0 is rejected. Because 0.00 < 0.05, which means that if the Sig (2-tailed) value < 0.05, then there is a difference between learning outcomes in the control class and the experimental class, and if the Sig (2-tailed) value is > 0.05, then there is no significant difference or influence between learning outcomes in the control class and the experimental class.